2006
DOI: 10.5194/acp-6-3035-2006
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous nucleation rates of nitric acid dihydrate (NAD) at simulated stratospheric conditions – Part II: Modelling

Abstract: Abstract. Activation energies G act for the nucleation of nitric acid dihydrate (NAD) in supercooled binary HNO 3 /H 2 O solution droplets were calculated from volume-based nucleation rate measurements using the AIDA (Aerosol, Interactions, and Dynamics in the Atmosphere) aerosol chamber of Forschungszentrum Karlsruhe. The experimental conditions covered temperatures T between 192 and 197 K, NAD saturation ratios S NAD between 7 and 10, and nitric acid molar fractions of the nucleating sub-micron sized droplet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
(118 reference statements)
1
17
0
Order By: Relevance
“…This finding is also supported by simulations of our experiments using a microphysical process model. The description and the results of these simulations where different parameterizations are compared to experimental data is the subject of the second part of this paper (Möhler et al, 2006). The findings in this study complement the results by Duft and Leisner (2004) where droplets with diameters of 40 µm and larger were used to study the homogeneous nucleation of ice.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This finding is also supported by simulations of our experiments using a microphysical process model. The description and the results of these simulations where different parameterizations are compared to experimental data is the subject of the second part of this paper (Möhler et al, 2006). The findings in this study complement the results by Duft and Leisner (2004) where droplets with diameters of 40 µm and larger were used to study the homogeneous nucleation of ice.…”
Section: Discussionsupporting
confidence: 73%
“…To overcome this difficulty the discussion of results can be moved from nucleation rates to the Gibbs free energies G act of critical cluster formation. This discussion is done thoroughly in the companion paper (Möhler et al, 2006). The surface nucleation rates which we obtained from our measurements are compared with the theory discussed in Tabazadeh et al (2002).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contradiction to CNT, Tabazadeh et al (2002) suggested that homogeneous nucleation is initiated close to surfaces. There is an ongoing debate on the validity of these mechanisms and the currently available data may not be sufficiently detailed to distinguish between the two hypotheses (Möhler et al, 2006a;Stetzer et al, 2006;Tabazadeh, 2005).…”
Section: Ice Nucleation In the Tropospherementioning
confidence: 99%